Alasan Kasasi Oleh Penuntut Umum Dalam Perkara Penggelapan Pada Hubungan Kerja Secara Berlanjut - A, Almarindra (Sebelas Maret University, 2017)
The aim of this research is to determine the suitability of legal arguments Supreme Court granted defendant's appeal in embezzlement case in the employment relationship continues with article 253 the Code of Criminal Procedure. The purpose of this study was to determine why the appeal by the Public Prosecutor and the consideration of Supreme Court judges in examining and deciding cases of embezzlement in office. Public Prosecutor considered that the judge misapplied the law to break the embezzlement case. based on the legal facts revealed in advance the trial turns out three evidences of a parcel of land and cash clearly derived from criminal acts committed by the defendant, and the absence of good faith the defendant to reimburse to the CV. Surya Prima Kertak Hanyar of total losses of Rp 1,213,596,000.00 (one billion two hundred and thirteen million five hundred ninety six thousand rupiah). Embezzlement in a continuing employment relationship is not a new thing in the community. Mode like this generally occurs within the scope of families, companies, and institutions in general. The results show that the facts and the evidence revealed the defendant had to account for his actions, according handed down by Judge to undergo imprisonment for four years. The reason of prosecutor appeal has qualified the qualification accordance with the provisions of Article 253 Criminal Procedure Code, by Judex factie otherwise there was an error regarding the evidence which is returned to the defendant that it is does not reflect the sense of justice that exist in society in general and very wounding taste justice for the victim witness namely CV. Surya Prima Kertak Hanyar. Overall consideration of the Supreme Court Judges examine and decide an appeal within the Public Prosecutor in the case of embezzlement in office in accordance with Article 256 Juncto Article 193 paragraph (1) Criminal Procedure Code. Grant the petition of appeal and cancel the earlier court decision. Keywords: Embezzlement, Cassation Reasons, Returns Evidence